A COMPUTER SIMULATION MODEL TO REDUCE PATIENT LENGTH OF STAY AND TO IMPROVE RESOURCE UTILIZATION RATE IN AN EMERGENCY DEPARTMENT SERVICE SYSTEM - Gul, Muhammet; Guneri, Ali Fuat (International Journal of Industrial Engineering: Theory, Applications and Practice, 2012)
This paper presents a case study of a discrete-event simulation (DES) model of an emergency department (ED) unit in a regional university hospital in Turkey. In this paper emergency department operations of the hospital were modeled, analyzed and improved. The goal of the study is to reduce patient average length of stay (LOS) and to improve patient throughput and utilization of locations and human resources (doctors, nurses, receptionists). Some alternative scenarios in an attempt to determine optimal staff level were evaluated. These alternative approaches illustrate that vital improvement in LOS and throughput can be obtained by minor changes in shift hours and number of resources. Considering future changes in patient demand a scenario which reduces LOS and improves throughput is available in the paper. Significance: The Key Performance Indicators (KPIs) to determine and improve system performance in healthcare emergency departments consist of to reduce patient average length of stay (LOS), to improve patient throughput and resource utilization rates. Alternative scenarios and optimal staff levels are enhanced within the scope of this study.